The Effect of Food Supplement MalnuForte on the Quality of Life of Children who Suffered Malnutrition in the First 1000 Days of their lives: A Case Report (MalnuForte Case Study) - Oort, T.A.J. van; Oort, J.M. van (International Journal of Child Health and Nutrition, 2019)
Objective: Malnutrition is a common worldwide problem and, for children, has a major impact on cognitive and physical development, productivity and health. The damage due to malnutrition is largest when it occurs in the first 1000 days of life. It is largely irreversible and has far-reaching consequences. There is as yet no known cure for the negative effects of malnutrition, while a cure for a large number of previously malnourished children worldwide would lead to better chances for them in life. This case study, therefore, examines the effect of a six-month treatment of MalnuForte on the quality of life of children between 5 and 11 years who suffered malnutrition in the first 1000 days of their lives Methods: The study subjects are five adopted children who suffered malnutrition in the first 1000 days of their lives and experienced problems or backlog in their quality of life. For six months, the children took one tablet of food supplement MalnuForte a day orally. To estimate the subjects’ quality of life, a standardized and validated quality of life questionnaire for children was used, the PedsQL. Results: A higher quality of life after six months was found for all subjects. The mean total increase of the PedsQL scores between baseline and 6 months was 50%. Conclusion: In this case study, the intake of food supplement MalnuForte shows remarkable increases in the quality of life of five adopted children who had suffered from malnutrition during the first 1000 days of their lives.